Comparative Study of Intravaginal Metronidazole and Triple-Sulfa Therapy for Bacterial Vaginosis. Issue 2 (1996) - Sobel, Jack D.; Chaim, Walter; Thomason, Jessica; Livengood, Charles; Sweet, Richard; McGregor, James A.; Eschenbach, David; Hillier, Sharon; Galask, Rudolph; Faro, Sebastian; Shangle, Elizabeth; Baker, David
Abstract : Objective: We sought to compare the efficacy of metronidazole gel vs. triple-sulfa cream in the treatment of bacterial vaginosis (BV). Methods: In a double-blinded study, 247 women with symptomatic BV were randomly assigned to receive either 5 g of 0.75% metronidazole gel twice daily for 5 days or triple-sulfa cream twice daily for 5 days. There were 205 (96 treated with metronidazole and 109 treated with triple-sulfa) evaluable patients to compare efficacy at the final visit. Approximately 60% of these patients had been previously treated for BV, reflecting the recurrent nature of the disease in this patient population. Results: At the first (12–16 days) return visit, 81/103 (79%) patients in the metronidazole group were cured compared with 80/113 (71%) patients in the triple-sulfa cream group ( P = 0.333). At the final (28–35 days) return visit, 63/96 (66%) in the 96 metronidazole group remained cured compared with only 51/109 (47%) in the triple-sulfa group ( P = 0.02). An intent-to-treat analysis similarly showed that the cure rate with metronidazole was superior to triple-sulfa ( P ≤ 0.02). The clinical diagnosis demonstrated a high correlation (88%) with the diagnosis made by an independent assessment by Gram's stain. The side effects reported by the patients using metronidazole gel were infrequent and mild and were similar to those reported with triple-sulfa. Conclusions: Metronidazole gel is a safe, effective, and well-tolerated treatment for BV.